Comprehensive Health Assessment 3 Months After Recovery From Acute Coronavirus Disease 2019 (COVID-19). (21st November 2020) - van den Borst, Bram; Peters, Jeannette B; Brink, Monique; Schoon, Yvonne; Bleeker-Rovers, Chantal P; Schers, Henk; van Hees, Hieronymus W H; van Helvoort, Hanneke; van den Boogaard, Mark; van der Hoeven, Hans; Reijers, Monique H; Prokop, Mathias; et al.
Abstract: Background: Long-term health sequelae of coronavirus disease 2019 (COVID-19) may be multiple but have thus far not been systematically studied. Methods: All patients discharged after COVID-19 from the Radboud University Medical Center, Nijmegen, the Netherlands, were consecutively invited to a multidisciplinary outpatient facility. Also, nonadmitted patients with mild disease but with symptoms persisting >6 weeks could be referred by general practitioners. Patients underwent a standardized assessment including measurements of lung function, chest computed tomography (CT)/X-ray, 6-minute walking test, body composition, and questionnaires on mental, cognitive, health status, and quality of life (QoL). Results: 124 patients (59 ± 14 years, 60% male) were included: 27 with mild, 51 with moderate, 26 with severe, and 20 with critical disease. Lung diffusion capacity was below the lower limit of normal in 42% of discharged patients. 99% of discharged patients had reduced ground-glass opacification on repeat CT imaging, and normal chest X-rays were found in 93% of patients with mild disease. Residual pulmonary parenchymal abnormalities were present in 91% of discharged patients and correlated with reduced lung diffusion capacity. Twenty-two percent had low exercise capacity, 19% low fat-free mass index, and problems in mental and/or cognitive function were found in 36% of patients. Health status was generally poor, particularly in the domains functional impairment (64%), fatigue (69%), and QoL (72%). Conclusions: This comprehensive health assessment revealed severe problems in several health domains in a substantial number of ex–COVID-19 patients. Longer follow-up studies are warranted to elucidate natural trajectories and to find predictors of complicated long-term trajectories of recovery. Abstract : Three months after recovery from acute coronavirus disease 2019 (COVID-19), this study shows that, while the pulmonary parenchyma is recovering, a substantial number of patients report severe problems in several health domains, including fatigue, functional impairment, and quality of life.